O trabalho dos operadores de máquinas colhedoras de cana-de-açúcar : uma abordagem ergonômica - Narimoto, Lidiane Regina (Universidade Federal de São Carlos, 2012)
Brazil is the largest producer of sugar cane in the world, making of this sector one of the most important agricultural activities in the country. Over recent years, the mechanization of sugarcane cutting has been regarded as an important tool to expand production and to meet worldwide demand. With mechanization, there are several new occupations, among them, the operation of harvesters machines, which plays a central role in the process. However, there is a lack of studies covering this work in its entirety. Therefore, the aim of this study was to analyze the work of sugarcane harvesters operators from the ergonomics standpoint in order to understand this activity, the constraints involved and the necessary expertise. For this purpose, the Ergonomic Work Analysis and its activity analysis was used as a research method. Operators from three sugar mills were studied, all the mills were located in Piracicaba/SP and two of them presented recent and developing mechanization process. For didactic purposes, the operator´s activity was described in three stages: the beginning of a line cut, the cut itself and the end of this. Then, this analysis was deepened, considering the most relevant factors in the operation. The methodological approach has highlighted the cognitive processes behind the activity, the complexity of the relationships at work as well as the influence of organizational aspects on labor and health. It was observed that the operators are subject to several constraints that require a continuous regulation process in order to maintain their health and achieve quantitative and qualitative results. Faced with many variabilities, the operators elaborate different operational strategies, several of them based on the cooperation relationship established with the tractor operator. The operator´s ability to handle all the variabilities of the situation and operate a complex machine in a safe and satisfactory way is gained with practice. It was concluded that the continuous regulation process developed by the operator ensures the quality of the product that arrives in the sugar mills.
Keywords: Ergonomia; Análise ergonômica do trabalho; Regulação; Mecanização agrícola; Máquina colhedora; Cana-de-açúcar; Ergonomic Work Analysis (EWA); Regulation; Sugarcane harvesters; Mechanization; Sugarcane.; ENGENHARIAS::ENGENHARIA DE PRODUCAO